2012
DOI: 10.4236/msa.2012.36054
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Properties of Mesoporous Mn-Co Oxide Derived from a Mixed Oxalate

Abstract: A mesoporous Mn-Co oxide for supercapacitors was derived from a mixed oxalate Mn<sub>0.8</sub>Co<sub>0.2</sub>C<sub>2</sub>O<sub>4</sub>·nH<sub>2</sub>O, which was synthesized by a solid-state coordination reaction at room temperature. The synthesized mixed Mn-Co oxalate was decomposed in air at 250°C, resulting in a tetragonal spinel Mn-Co oxide with a primary particle size less than 100 nm. The obtained Mn-Co oxide presents a mesoporous texture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As substituted atoms play as defects in each structure, the conductivity is increased . It has been also reported that Co mixed oxide composites exhibit superior capacitive performance to single metal oxides, Mn, Ni, and so forth. Likewise, the incorporation of Co (or Ir) into the other framework possibly results in increased conductivity of Ir x Co 1– x O y nanocomposites.…”
Section: Resultsmentioning
confidence: 98%
“…As substituted atoms play as defects in each structure, the conductivity is increased . It has been also reported that Co mixed oxide composites exhibit superior capacitive performance to single metal oxides, Mn, Ni, and so forth. Likewise, the incorporation of Co (or Ir) into the other framework possibly results in increased conductivity of Ir x Co 1– x O y nanocomposites.…”
Section: Resultsmentioning
confidence: 98%
“…The electrolyte used was aqueous solution of 1 M Na 2 SO 4 . The performance of supercapacitor studies were evaluated by cyclic voltammetry (CV) and galvanostatic chargedischarge techniques within the potential range between 0 and 1 V at different scan rates (5,10,20,40, 80 and 160 mV s À1 ) and different current densities (0.5-15 mA cm À2 ) respectively. Electrochemical impedance spectroscopy measurements were performed under open circuit voltage in an alternating current frequency range of 0.1-100 000 Hz with an excitation signal of 10 mV.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…2,3 Generally the supercapacitors can be classied into two categories based on the charge storage mechanism: (i) electrochemical double-layer capacitors (EDLCs), which are based on electrostatic charge diffusion and accumulation at the electrode/electrolyte interface, 4 (ii) pseudocapacitors, which are based on reversible faradic redox reactions at the electrode/electrolyte interface. 5 In recent years, a signicant amount of effort has been assigned to improve the electrochemical performance of electrode materials in order to develop better supercapacitors with both high power and energy densities. 6 To date, the electrode materials used for supercapacitors are carbon materials (activated carbons, 7 carbon fabrics, 8 carbon nanotubes, 9 etc.…”
Section: Introductionmentioning
confidence: 99%
“…If each Mn atom is supposed to store one electron, then the specific capacitance of MnO 2 will be 1370 F g −1 . A variety of approaches have been developed for manganese oxide preparation, including precipitation [9], electrodeposition, sol−gel method, thermal decomposition, solid state reaction, hydrothermal synthesis, and pulsed laser deposition (PLD) . However, manganese oxide suffers from the poor electrical conductivity causing the pseudocapacitive redox reaction be confined to a very thin surface layer and the ideal performance of MnO x is only observed with an extremely thin oxide layer .…”
Section: Introductionmentioning
confidence: 99%